Antiques con [large type] - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2014)
A world away from small-town Serenity, Brandy Borne and her drama-queen mom -- chaperoned by their trusty shih tzu, Sushi -- arrive in the Big Apple for a comic-book convention to sell a rare 1940s Superman drawing. When an intruder breaks into their suite, they naturally suspect a felonious fan. Instead they stumble onto a murder victim impaled by a pen-shaped award and are led on a merry madcap Manhattan misadventure.